Effect of Surgical Treatment for Deep Infiltrating Endometriosis on Pelvic Floor Disorders: A Systematic Review with Meta-analysis - Fraga, Mirian Vieira; Benetti-Pinto, Cristina Laguna; Yela, Daniela Angerame; Mira, Ticiana Alves de; Brito, Luiz Gustavo Oliveira (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objectives To evaluate the impact of surgical treatment of deep infiltrative endometriosis (DIE) on pelvic floor dysfunction (urinary incontinence [UI], pelvic organ prolapse [POP], fecal incontinence [FI)] or constipation, and sexual function [dyspareunia]).Data Source The present systematic review was performed in the PubMed database. For the selection of studies, articles should be published by January 5, 2021, without language restriction.Study Selection Six randomized controlled studies that evaluated surgical treatment for DIE and the comparison of different surgical techniques were included.Data Collection The studies were selected independently by title and abstract by two authors. Disagreements were resolved by a third author. All included studies were also evaluated according to the Cochrane risk of bias tool and the quality of the evidence was analyzed using the GRADE criteria. Subgroup analysis by different treatments and follow-up periods was also performed.Results Six studies were included in the quantitative analysis. The risk of bias between studies showed an uncertain risk of bias for most studies, with concealment of allocation being the least reported category. The quality of the evidence was considered low. High heterogeneity was found between the studies. No study has evaluated UI or POP comparatively before and after surgery.Conclusion Dyspareunia and FI have improved after the surgical procedure, but it was not possible to demonstrate which surgical technique was related to these outcomes as there was surgical heterogeneity. This diversity was found across data, with the recommendation of future prospective studies addressing pelvic floor disorders with DIE.
Keywords: systematic review; endometriosis; fecal incontinence; urinary incontinence; pelvic floor